Crises as Catalyst: A New Social Contract Grounded in Worker Rights - Diane F. Frey; Gillian Macnaughton; Andjela H. Kaur; Elena K. Taborda (Harvard FXB Center for Health and Human Rights, 2020)
Three crises-climate change, the COVID-19 pandemic, and extreme economic and social inequality-intersect and have had devastating impacts on workers' rights to health, as well as the right to decent work, an underlying determinant of health. Yet these crises may act as catalysts, as responses present opportunities for transformation. Indeed, multiple international governance institutions and nongovernmental organizations have proposed new social contracts that aim to address the multiple challenges facing workers today. These initiatives promise to transform society to make workers and their families healthier and the planet more sustainable. They join and supplement earlier efforts at transformation, such as the 2030 Agenda for Sustainable Development. This article critiques (1) the market-fundamentalist neoliberal social contract, which gave rise to, or exacerbated, the three crises, and (2) the 2030 agenda and recent International Labour Organization proposals, which are all built on this neoliberal platform. Finally, the article argues for a social contract that is grounded in human rights-specifically worker rights-to address these crises and ensure greater protection of the health